Asymmetric Autoamplification in the Oxidative Kinetic Resolution of Secondary Benzylic Alcohols Catalyzed by Manganese Complexes. Issue 13 (9th June 2017) - Talsi, Evgenii P.; Samsonenko, Denis G.; Bryliakov, Konstantin P.
Abstract: Herein, chiral Mn–aminopyridine complexes have been shown to catalyze the oxidation of alkylarenes to enantiomerically enriched 1‐arylalkanols with hydrogen peroxide. The observed enantiomeric excess values result from the direct enantioselective benzylic C−H hydroxylation, accompanied by stereoconvergent oxidative kinetic resolution of the resulting alcohol. Testing several ( S, S )‐bipyrrolidine derived Mn complexes has revealed a novel catalyst (6 ) that exhibits the best kinetic resolution in the series ( k rel up to 8.8), along with sufficient reactivity and efficiency (>1000 catalytic turnovers). The mechanistic study of the Mn‐mediated alcohol oxidation witnesses electrophilic active species ( ρ =−1.2), with rate‐limiting H abstraction ( k H / k D =2.2), followed by oxygen rebound and dehydration of the resulting gem ‐diol to form the ketone. Intriguingly, while for the resolution of the relatively bulky 1, 2‐diphenylethanol, k rel is virtually constant throughout the reaction, for less bulky alcohols, k rel increases with increasing conversion, in line with the rising optical purity of the 1‐arylalkanol. The latter participates in the oxidation as an auxiliary ligand, assisting the chiral recognition. This effect is related to the previously described asymmetric autocatalysis and asymmetric autoinduction, but is not identical with either of those, with the differences being discussed. To unambiguously identify this effect, the term asymmetric autoamplification ( chiral autoamplification ) is proposed. Abstract : Substrate enhanced kinetic resolution : Oxidative kinetic resolution of 1‐arylethanols in the presence of chiral Mn–aminopyridine catalysts has been shown to be affected by coordination of the substrate to the catalytically active sites, which results in monotonous increase of the k rel with increasing conversion. To identify this effect, the term asymmetric autoamplification is proposed.